The SLEM Model as an Assessment Method for Local Goods’ Competitiveness - Bartha, Zoltán; Molnár, László (Theory, Methodology, Practice – Review of Business and Management, 2016)
In this paper we develop and present the SLEM model created to measure the market potential of local goods supplied by the entrepreneurs of the Cserehát region, one of the most deprived regions of Hungary. The SLEM model evaluates goods along four dimensions: supplier conditions, labour conditions, (professional) embeddedness, and market conditions. The four pillars were measured with factors that are easily accessible, and so the evaluation can be repeated with other regions as well. In case of Cserehát, we have identified the following five groups of local goods with the greatest potential: animal husbandry; honey; spices and pharmaceutical crops; nature tourism; and mineral water.